USING COMPETENCE, AUTONOMY AND RELATEDNESS (CAR) PRINCIPLES IN TEACHING READING - Prayogo, Agus (ENCOUNTER, 2012)
To be a good reader, student must be highly motivated and practice consistently. The purpose of this article is to justify how the use of competence, autonomy, and relatedness (CAR) principles in teaching reading will improve the studentsâ motivation to read. As a behavioral construct, motivation sustains interest in learning that can drive the successful learning ability. Therefore, learning should be supported with psychological needs such as competence, autonomy and relatedness to increase motivation. The competence-based activities would create challenging and not devastating activity that enables students to complete the tasks. Autonomy enables students to control their own behavior. Relatedness lets students work together with people around them.